2019
DOI: 10.1111/trf.15150
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro pilot study of apheresis platelets collected on Trima Accel system and stored in T‐PAS+ solution at refrigeration temperature (1‐6°C)

Abstract: BACKGROUND Using platelet additive solution (PAS) to dilute fibrinogen during long‐term cold storage of platelets (PLTs) decreases PLT activation and increases functional PLT shelf life. We performed a randomized, paired study to assess the in vitro quality of PLTs stored in the cold in T‐PAS+ for up to 18 days evaluated against PLTs stored under currently allowable conditions (5‐day room temperature–stored PLTs [RTP] and 3‐day cold‐stored PLTs [CSP]). STUDY DESIGN AND METHODS PLTs were collected from healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 21 publications
4
25
0
Order By: Relevance
“…In our experiments, addition of VX-702 resulted in increased HSR levels of cold-stored and thermocycled-stored platelets. After one week of storage, room-stored platelets maintained HSR levels better than any cold conditions, as has been described in the literature [14,17,29,30,40]. However, after two weeks of storage, HSR levels were better preserved during storage at cold and thermocycled temperatures than at room temperature and this was further improved in presence of VX-702.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In our experiments, addition of VX-702 resulted in increased HSR levels of cold-stored and thermocycled-stored platelets. After one week of storage, room-stored platelets maintained HSR levels better than any cold conditions, as has been described in the literature [14,17,29,30,40]. However, after two weeks of storage, HSR levels were better preserved during storage at cold and thermocycled temperatures than at room temperature and this was further improved in presence of VX-702.…”
Section: Discussionsupporting
confidence: 73%
“…Cold temperature storage also generates changes in cell surface glycoprotein glycosylation, GPIbα clustering [ 11 , 12 ] and transforms integrin αIIbβ3 conformation to an activated state [ 13 ]. Similarly, cold storage manifests in platelet activation which results in lysosomal and granule release [ 13 ] as well as increased microparticle formation [ 14 ]. Overall, the cold storage lesion appears to make platelets more procoagulant [ 15 ] and likely to be effective when transfused into actively bleeding patients [ 16 ] even though their circulation time is reduced [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 RTP in PAS retracted for up to 21 days while those stored in AP failed to retract past 10 days, likely due to the better buffering capability and metabolic support provided by PAS over plasma. [30][31][32][33] Interestingly, we observed an increase in retraction in 5-day RTP in AP and PAS independent of platelet or fibrin incorporation, while these platelets generated 50% less contractile stress than fresh platelets indicating semifunctional contractile machinery at 5 days of storage. This suggested that the seemingly increased retraction is not a function of platelet contractility, prompting a deeper investigation of clot microstructure and serum composition.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, Filip and Aster 15 found that cold‐stored PLTs were less effective after 72 hours of storage when compared to RT‐stored PLTs in vivo. Multiple in vitro studies have shown that PLTs maintain good hemostatic properties when stored for periods of up to 21 days in cold conditions, 16–19 but these studies have not yet identified the root cause of why long‐term (>5 days) cold‐stored PLTs do not function as well as those stored short term (<3 days).…”
Section: Introductionmentioning
confidence: 99%